2016
DOI: 10.18632/oncotarget.8955
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic ALK regulates EMT in non-small cell lung carcinoma through repression of the epithelial splicing regulatory protein 1

Abstract: A subset of Non-Small Cell Lung Carcinoma (NSCLC) carries chromosomal rearrangements involving the Anaplastic Lymphoma Kinase (ALK) gene. ALK-rearranged NSCLC are typically adenocarcinoma characterized by a solid signet-ring cell pattern that is frequently associated with a metastatic phenotype. Recent reports linked the presence of ALK rearrangement to an epithelial-mesenchymal transition (EMT) phenotype in NSCLC, but the extent and the mechanisms of an ALK-mediated EMT in ALK-rearranged NSCLC are largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 61 publications
0
24
1
Order By: Relevance
“…All patients with ALK-rearrangements had higher proportion of vim+ CTCs in relation to total CTCs. However, no significant correlation with ALK-rearrangement and vimentin expression was observed which is in discordance with the data from other studies where EMT was associated with the response to treatment with ALK inhibitors (23,24). In the EGFR-assessed group, EGFR mutated patients had both significantly higher total CTC and vim+ CTC positivity than EGFR wt patients (P=0.038 and P=0.013, respectively).…”
Section: Editorialcontrasting
confidence: 75%
“…All patients with ALK-rearrangements had higher proportion of vim+ CTCs in relation to total CTCs. However, no significant correlation with ALK-rearrangement and vimentin expression was observed which is in discordance with the data from other studies where EMT was associated with the response to treatment with ALK inhibitors (23,24). In the EGFR-assessed group, EGFR mutated patients had both significantly higher total CTC and vim+ CTC positivity than EGFR wt patients (P=0.038 and P=0.013, respectively).…”
Section: Editorialcontrasting
confidence: 75%
“…EML4-ALK regulates EMT phenotype and represses ESRP1 in nonesmall cell lung carcinoma. 22 ESRP1 knockdown impaired E-cadherin up-regulation on ALK inhibition, whereas enforced expression of ESRP1 was sufficient to increase E-cadherin expression. These results indicated that ESRP1 is a key regulator of the EMT phenotype induced by oncogenic ALK in normal and cancer lung epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…The ESRP1 gene was also found to be the target of biallelic inactivating mutations in human colon cancers with microsatellite instability [13]. In agreement with the tumor suppressive role of ESRP1, several studies have shown that ESRP1 negatively regulates Epithelial-to-Mesenchymal Transition (EMT) in breast and pancreatic cancer, in oral squamous cell and non-small cell lung carcinomas [14,15,16,17]. Paradoxically, however, a pro-metastatic activity of ESRP1 has also been reported.…”
Section: Introductionmentioning
confidence: 97%